Diagnosis and Management of Antepartum Bleeding in Primary Health Care - Winata, I Gde Sastra; Mahendrata, Prayascita; Intizam, Marwa Humaira; Astawa, I Made Mulya (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Objective: Antepartum bleeding, occurring in the second or third trimester of pregnancy, is a critical obstetric concern. This literature review explores diagnostic and management strategies for antepartum bleeding within primary health care settings. Method: This study employs a literature review methodology. Data were gathered from articles published between 2010 and 2024, accessed through PubMed and ScienceDirect.Result: Early identification and timely management of antepartum bleeding are essential in minimizing maternal and fetal morbidity and mortality. This review examines diagnostic approaches, including clinical assessments, ultrasonography, and laboratory investigations, with a focus on their accessibility within primary care environments. Management strategies, ranging from expectant care to emergency interventions, are discussed, alongside the critical role of primary care providers in stabilizing patients, ensuring prompt referrals, and providing continuous care.Conclusion: The review concludes by advocating for standardized protocols and enhanced training for primary care practitioners to improve the management of antepartum bleeding.Diagnosis dan Penatalaksanaan Perdarahan Antepartum di Layanan Kesehatan PrimerAbstrakTujuan: Perdarahan antepartum, yang terjadi pada trimester kedua atau ketiga kehamilan, merupakan perhatian serius dalam perawatan obstetri. Tinjauan literatur ini mengeksplorasi strategi diagnosis dan penatalaksanaan perdarahan antepartum di layanan kesehatan primer. Metode : Penelitian ini merupakan literatur review. Data penelitian diperoleh dari publikasi artikel di tahun 2010 – 2024 yang diakses melalui PubMed and ScienceDirect. Hasil: Identifikasi dini dan penatalaksanaan tepat waktu sangat penting untuk meminimalkan morbiditas dan mortalitas ibu serta janin. Pendekatan diagnostik, termasuk penilaian klinis, ultrasonografi, dan pemeriksaan laboratorium, ditinjau dengan penekanan pada aksesibilitasnya di lingkungan pelayanan primer. Selain itu, protokol manajemen, mulai dari penanganan ekspektatif, hingga intervensi darurat juga diulas. Peran penyedia layanan kesehatan primer dalam menstabilkan pasien, memastikan rujukan tepat waktu, dan memberikan perawatan lanjutan sangat ditekankan. Kesimpulan: Tinjauan ini menyimpulkan dengan menganjurkan adanya protokol standar dan peningkatan pelatihan bagi praktisi layanan kesehatan primer untuk lebih baik menangani perdarahan antepartum.Kata kunci : Antepartum, gawat darurat, kehamilan, perdarahan